Isochoric generation and spectroscopic diagnosis of high energy-density systems - Humphries, O (2020)
Advances in both optical laser and X-ray Free Electron Laser (XFEL) facilities have extended the regimes accessible in laser targets. Petawatt lasers such as Orion at AWE can be routinely used to drive targets to extreme conditions of multi-keV temperatures. Isochoric heating with an XFEL to temperatures of 100’s of eV has been demonstrated and well described on prototypical metals and low-Z mixtures, and the bright, tunable x-ray source is often used as a probe in Warm Dense Matter (WDM) and High Energy-Density (HED) studies. X-ray diagnostics are often used to characterise the conditions present in such a laser target, with stringent demands on collection efficiency to yield significance in signal/noise in order to characterise systems with potentially large spatio-temporal gradients. This thesis describes a set of experiments to isochorically generate and characterise WDM and HED systems relevant to astrophysical plasmas and Inertial Confinement Fusion. The focus of this work is on using measured X-ray Emission Spectroscopy or Resonant Inelastic X-ray Scattering (RIXS) spectra to bound the conditions present in the laser target, and using Single Photon Counting informed techniques to maximise the signal/noise in recovered spectra. Accurate accounting of the single photon response of x-ray detectors is used to detail the absolute value and error on recovered spectral intensity, and from that to inferred plasma parameters. The particular systems considered in this work are nanowire targets irradiated at relativistic intensities, RIXS measurements of warm-dense nickel, and nano-focused XFEL heating of solid density iron.